Cyp1 Inhibition Prevents Doxorubicin‐Induced Cardiomyopathy in a Zebrafish Heart‐Failure Model. (8th June 2020) - Lam, Pui‐Ying; Kutchukian, Peter; Anand, Rajan; Imbriglio, Jason; Andrews, Christine; Padilla, Hugo; Vohra, Anita; Lane, Sarah; Parker, Dann L.; Cornella Taracido, Ivan; Johns, Douglas G.; Beerens, Manu; et al.
Abstract : Cyp1 inhibition prevents doxorubicin‐induced cardiomyopathy in a zebrafish heart‐failure model. Doxorubicin, a potent chemotherapy drug, has a side effect of inducing heart failure. By using a zebrafish doxorubicin‐induced cardiomyopathy model for in vivo small‐molecule screening, the cytochrome P450 family (CYP1) was identified as a candidate therapeutic target for clinical cardioprotection. More information can be found in the full paper by R. T. Peterson et al.